Declining populations of greater sage-grouse: where and why - Michael R. Conover; Anthony J. Roberts (Human-Wildlife Interactions, 2017)
Scientists have been predicting the extinction of greater sage-grouse (Centrocercus urophasianus) since 1916, and sage-grouse populations have declined relentlessly during the last century despite attempts to reverse the decline. In this review paper, we examined the scientific literature to evaluate hypotheses about why sage-grouse populations have declined. There is little support for the hypotheses that the decline is due to overhunting, parasites, food shortages, or collisions with power lines or fences. West Nile Virus (WNV) reduced sagegrouse up to 25% when the virus first reached the West during 2002, but sage-grouse have developed resistance to the virus since then, rendering the virus less virulent. Golden eagles (Aquila chrysaetos), great horned owls (Bufo virginianus), and coyotes (Canis latrans) kill many adult sage-grouse, but populations of these predators have not increased during the last century, so predation by these predators probably have not contributed to the decline. In contrast, common ravens (Corvus corax) have become more numerous in the West, and nesting success of sage-grouse is higher in areas where raven numbers are low or have decreased. Sage-grouse broods often forage in wet meadows that are interspersed among the sagebrush (Artemisia spp.), but many of these wet areas have converted into pastures and alfalfa fields. Local populations of sage-grouse have collapsed when sagebrush habitat is eliminated due to fi re, development, or conversion to pasture or farmland. Areas where sagegrouse have been extirpated are along the periphery of the sage-grouse’s range, have more people, have less sagebrush, and have lost much of the sagebrush that once existed there. Hence, the decline of sage-grouse populations can be attributed, at least in part, to the loss of large stands of sagebrush, but just why large stands are important is unclear.